The Ebola contagion and forecasting virus: Evidence from four African countries - Selmi Nadhem; Hachicha D. Nejib (Health Economics Review, 2015)
This paper is focused on examining the number of deaths' increases participation in the propagating the Ebola virus during the period ranging from March to October 2014. An application of the MGARCH-DCC model regressions on four countries has led to discover that the finding that human contact play a significant role in transmitting the Ebola virus. Our findings also reveal that Guinea has already suffered from a spread-like virus originating from Sierra Lione and Liberia. Noteworthy also, other countries are now liable to such a risk; for instance, Nigeria is a country vulnerable to the propagation of this virus. Consequently, we undertake to conduct our forecasts for EGARCH model estimates implements; which has estimated a decrease in the Ebola virus incurred number of deadly Ebola virus over the two months following the November and December.
Keywords: 330; Ebola 2014; Contagion; Virus; EGARCH; MGARCH-DCC